Perception of young Muslim men towards sexual reproduction, contraception and child rearing in Kalibo, Aklan - Dugang, Daryl D.
This is a descriptive study aimed to determine the perception of young Muslim men towards sexual reproduction, contraception in child rearing in Kalibo, Aklan., Results from convenient sampling of 31 respondents aging 16 to 24 revealed that except for gender issues, majority of the Fil-Muslim men were held conservative views towards sexual permissiveness, coercion/violence, peer influence and abortion. Most of the respondents were sexually active but were using contraceptives. Almost all of them know the nature of contraceptive methods and its accessibility. In terms of child rearing roles, the respondents perceived the fathers to be punisher, protector and provider while the mothers remain to be nurturing figure in the family